Brand capital and debt choice - Sabri Boubaker (International Review of Financial Analysis, 2024)
This paper investigates the effect of brand capital on firms' choices of debt structure. Using a sample of publicly listed U.S. firms between 2001 and 2019, we find that firms with higher levels of brand capital rely less on bank debt financing. This finding is robust to the use of alternative regression models and alternate measures of brand capital and bank debt financing. Employing an industry-level positive shock to brand capital as a quasi-natural experiment, we demonstrate that such a shock negatively affects firms' reliance on bank debt. Our cross-sectional analyses reveal that the effect of brand capital on bank debt is more pronounced for firms with high information asymmetry, weak corporate governance mechanisms, and poor financial conditions. We also find that brand capital-intensive firms raise funds from the public debt market and issue more (or less) unsecured (or secured) debt. Taken together, we show that brand capital has an important bearing on corporate financing decisions.